Genetic Interaction Between Two VNTRs in the SLC6A4 Gene Regulates Nicotine Dependence in Vietnamese Men - Kõks, Gea; Prans, Ele; Tran, Ha Diep Thi; Ngo, Ngoc Bich Thi; Hoang, Linh Nhat Nguyen; Tran, Hue Minh Thi; Cao Ngoc, Thanh; Doan Phuoc, Thuoc; Ho, Xuan Dung; Ho Duy, Binh; Lättekivi, Freddy; Quinn, John; et al. (Frontiers in Pharmacology, 2018)
Two variable number tandem repeat (VNTR) domains, termed HTTLPR and STin2, in the SLC6A4 gene are well characterised transcriptional regulatory elements of SLC6A4 transcription. Their polymorphism in the copy number of the repeat is correlated with certain personality and psychiatric traits. Association between SLC6A4 and nicotine dependence is controversial. We analysed nicotine dependence in 1,804 participants from Central Vietnam. The Fagerström Test (FTND) was used to evaluate the nicotine dependence with the genotype of the SLC6A4 HTTLPR and STin2 VNTRs. The HTTLPR VNTR was associated with difficulties to refrain from smoking in a prohibiting environment. The STIn2 10/10 genotype was associated with 1) years of smoking, 2) difficulties to quit first cigarette and 3) higher number of cigarettes smoked per day (CPD). Stratification analysis was used to find the genetic interaction between these two VNTRs in nicotine dependence as they may synergistically regulate thhe SLC6A4 expression. Smokers with the S/S HTTLPR genotypes showed much stronger association between STin2 10/10 variant and CPD. This finding is consistent with the molecular evidence for the functional interaction between HTTLPR and STin2 in cell line models, where STin2 has described as stronger expressional regulator. Similarly, we found that STin2 is a much stronger modifier of smoking with 10/10 genotype related to higher nicotine dependence. Present study supports genetic interaction between HTTLPR and STin2 VNTRs in the regulation of nicotine dependence with dominance of the STin2 effects. This finding could be explained by their differential effect on the SLC6A4 expression.